CONTROLLED CLINICAL EVALUATION OF MAMAJJAK CHOORNA IN STHULA MADHUMEHA VIZ-A-VIZ TYPE 2 DIABETES MELLITUS - Shankarrao, Surse Yogesh; Raut, Aparna; Vaibhav D, Phartale; Kiran P, Shinde (International Journal of Ayurveda and Pharma Research, 2017)
Sthula Madhumeha (viz-e-viz type 2Diabetes Mellitus) is the vital problem in present era. The change in lifestyle and food habit is the major concern of the problem. The available drug therapy concentrating on levels of blood sugar rather than symptoms of patients like excessive thirst, Nocturnal enuresis, burning sensation in hands, feet and many more. Ayurveda emphasized more on these symptoms. These symptoms affects the patients routine life and work capacity. On behalf of these symptoms the role of Mamajjak Choorna which is described by Acharya Priyavrat Sharma in his book Dravya guna Vidnyan Vol. 2 page 705 found to be more effective in comparison to modern oral hypoglycemic and well practiced drug Metformin. Total 40 patients of newly diagnosed of Diabetes Mellitus were taken and divided in two groups as Trial group 20 patients on Mamajjak Choorna 5 gm B.I.D. given for 12 weeks. Control Group 20 patients on tab. Metformin 500 mg B.I.D. given for 12 weeks.On consumption of Mamajjak Choorna for 12 weeks it was found that there is improvement in the symptoms Pipasati Pravrutti (74.27%), Nakta mutrata (83.33%), Hasta-padatala daha (82.5%) Pippalika Sancharvaat prachti (85.71%), Prabhuta Avila mutrata (77.5%), Swedatipravritti (82.5%) so far as consumption of Metformin is concern, it was found as follows Pipasati Pravrutti (64.71%), Nakta mutrata (72.94%), Hasta-padatala daha (51.28%), Pippalika Sancharvaat prachti (50%), Prabhuta Avila mutrata (71.88%), Swedatipravritti (51.16%). With P<0.05 (that highly significant results in Mamajjak Choorna group).